An m-leaming game for the study of humanities - Banerjee, Snehasish (2016)
Unlike the hard sciences, the study of humanities has not adequately leveraged on technologies such as mobile learning and serious games. Hence, this paper introduces SingaRacer, a mobile learning game to study humanities, specifically, history and culture. The ways in which users might perceive its prospect both as a game as well as an educational application was examined. For this purpose, SingaRacer was evaluated through a user study comprising 52 participants. Their intention to use SingaRacer was generally promising. Implications of the findings are highlighted.